Panchromatic sensitizer for dye-sensitized solar cells: un-symmetrical squaraine dyes incorporating benzodithiophene π-spacer with alkyl chains to extend conjugation, control the dye assembly on TiO2 and retard charge recombination - Bisht, Rajesh; Munavvar, Fairoos Mk; Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (Journal of Organic Chemistry, 2017)
Metal-free near-infrared (NIR) active unsymmetrical squaraine dyes, RSQ1 and RSQ2, with benzodithiophene (BDT) π-spacer and cyanoacrylic acid acceptor were synthesized by utilizing palladium catalyzed direct (hetero)arylation reaction. Methyl and 2-ethylhexyl groups were strategically placed at the BDT unit for RSQ1 and RSQ2 respectively, to investigate the effect of alkylated π-spacer on dye aggregation on the TiO2 surface and recombination reactions at TiO2/dye/electrolyte interface. These dyes have strong absorption ( ε>10(5) M(-1)cm(-1)) in near-infra red (NIR) region and exhibit similar optical and electrochemical properties as they have same conjugated framework. RSQ2 performed better than RSQ1 owing to its higher open-circuit voltage (Voc) and fill factor (ff) in spite of having comparable short-circuit current density (Jsc). The panchromatic incident photon-to-current conversion efficiency (IPCE) response was also observed for both the dyes. RSQ2 showed power conversion efficiency (PCE) of 6.72% with short-circuit current density (Jsc) of 18.53 mA/cm(2), open circuit voltage (Voc) of 0.538 V, and fill factor (ff) of 67.4%, without any co-adsorbent. Attenuation of the charge recombination for RSQ2 was revealed by electrochemical impedance analysis (EIS) and open-circuit potential decay transients (OCVD), which attributes to its higher Voc and ff in comparison to RSQ1.